Teacher Support Strategies in Developing the Social-Emotional Development of Active Early Childhood Children - Dwi Nur Cahyani; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to analyze teacher mentoring strategies in developing the social-emotional development of active early childhood in Darma Putra Playgroup. The background of this study is based on the findings of children with high levels of activity who show difficulties in self-regulation, impulse control, and social interaction, such as snatching toys and disturbing friends. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of one child with active characteristics, the class teacher, and parents. Data analysis was carried out through data reduction, data presentation, and triangulation of conclusions. The results of the study indicate that teacher mentoring strategies through directed play, familiarization with class rules, positive reinforcement, and individual mentoring are able to improve self-regulation skills, sharing skills, and the ability to wait for turns. The child's social-emotional development score increased from the category of "Not Developing" to "Developing According to Expectations." These findings confirm that consistent and responsive teacher mentoring strategies contribute significantly to the active social-emotional development of early childhood.